Computational study of the aerodynamic of high-speed train [compact disc] - 213574 Mohd. Rafie Adni (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Automotif)) - Universiti Teknologi Malaysia, 2006